CONTINUOUS EVALUATION APPROACH: CONTROL STRATEGIES TOWARDS PROGRAM SUCCESS - Eva Rosdiana; Antonius Totok Priyadi; Khairullah (International Journal of Teaching and Learning, 2025)
Continuous evaluation is a strategic approach that places the evaluation process as an iterative and integrated cycle in each program stage. This article analyzes how continuous evaluation can serve as an effective control strategy towards program success. Using a qualitative research method based on case studies, data is obtained through interviews, observations, and document analysis, which is then analyzed thematically. The study results show that continuous evaluation strengthens program control through early detection of problems, improved decision-making quality, and resource use efficiency. In addition, the participation of external stakeholders has been proven to increase the legitimacy of the evaluation results while strengthening the sense of ownership of the program. Organizational culture factors also play an important role, where a culture of learning and openness has been shown to support the effectiveness of evaluations. These findings confirm that continuous evaluation serves as a technical instrument and a social and strategic mechanism in maintaining the program's success. The practical implications of this study are the importance of integrating evaluation into management control systems, while its theoretical implications encourage the development of more participatory and adaptive evaluation models. Thus, continuous evaluation can be a catalyst for innovation and consistent improvement of program quality.